2022
DOI: 10.1007/s13205-022-03115-4
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of mechanistic approaches of rhizosphere microorganisms facilitated plant health and resilience under challenging conditions

Abstract: Delineation of mechanistic approaches of rhizosphere microorganisms facilitated plant health and resilience under challenging conditions. 3 Biotech, 12(3), 57.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 331 publications
0
4
0
Order By: Relevance
“…Their ability to withstand disturbance and ward off invasive species may be assisted by the activation of genes involved in resource allocation, resource defence, and the stress response (Guggisberg et al, 2013). In native weed communities, transcriptomic investigations have revealed that the expression of stress-responsive genes (Jahan et al, 2022), such as those encoding heat shock proteins or antioxidants, increases in response to disturbances (Khattak et al, 2022(Khattak et al, , 2023aDukare et al, 2022), enabling them to maintain their competitive advantage (Meena et al, 2017). The invasive weed purple loosestrife, Lythrum salicaria, can change the expression of genes involved in resource acquisition, enabling it to supplant native species (Daehler, 2003).…”
Section: Omics Approaches Informing Plant Invasion Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their ability to withstand disturbance and ward off invasive species may be assisted by the activation of genes involved in resource allocation, resource defence, and the stress response (Guggisberg et al, 2013). In native weed communities, transcriptomic investigations have revealed that the expression of stress-responsive genes (Jahan et al, 2022), such as those encoding heat shock proteins or antioxidants, increases in response to disturbances (Khattak et al, 2022(Khattak et al, , 2023aDukare et al, 2022), enabling them to maintain their competitive advantage (Meena et al, 2017). The invasive weed purple loosestrife, Lythrum salicaria, can change the expression of genes involved in resource acquisition, enabling it to supplant native species (Daehler, 2003).…”
Section: Omics Approaches Informing Plant Invasion Mechanismsmentioning
confidence: 99%
“…Natural selection acts on genetic variation that allows individuals to respond to environmental fluctuations (Jump, Marchant & Peñuelas, 2009; Irimia et al ., 2023). Thus, adaptation of native weeds to local environments is evidence of their evolutionary success (Edwards et al ., 2018; Mable, 2019; Dukare et al ., 2022).…”
Section: Native Weed Communities Their Roles In Ecological Succession...mentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions of root-associated microorganisms are considered to be the root microbiota [ 2 ]. The root microbiota is essential to plant health, growth, and development and plays an important role by modulating plant hormone homeostasis, promoting nutrient acquisition, and improving resilience to abiotic or biotic stresses [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%